Primary human bronchial epithelial cell responses to diesel and biodiesel emissions at an air-liquid interface. (June 2019) - Vaughan, Annalicia; Stevanovic, Svetlana; Jafari, Mohammad; Bowman, Rayleen V.; Fong, Kwun M.; Ristovski, Zoran D.; Yang, Ian A.
Abstract: Introduction: Diesel emissions have a high level of particulate matter which can cause inflammation and oxidative stress in the airways. A strategy to reduce diesel particulate matter and the associated adverse effects is the use of biodiesels and fuel additives. However, very little is known about the biological effects of these alternative emissions. The aim of this study is to compare the effect of biodiesel and triacetin/biodiesel emissions on primary human bronchial epithelial cells (pHBECs) compared to diesel emissions. Methods: pHBECs were exposed to diesel, biodiesel (20%, 50% and 100% biodiesel derived from coconut oil) and triacetin/biodiesel (4% and 10% triacetin) emissions for 30 min at air-liquid interface. Cell viability (cellular metabolism, cell death, CASP3 mRNA expression and BCL2 mRNA expression), inflammation (IL-8 and IL-6 secretion), antioxidant production (HO-1 mRNA expression) and xenobiotic metabolism (CYP1a1 mRNA expression) were measured. Results: Biodiesel emissions (B50) reduced cell viability, and increased oxidative stress. Triacetin/biodiesel emissions (B90) decreased cell viability and increased antioxidant production, inflammation and xenobiotic metabolism. Biodiesel emissions (B100) reduced cell viability, and increased IL-8 secretion and xenobiotic metabolism. Conclusions: Biodiesel substitution in diesel fuel and triacetin substitution in biodiesel can increase the adverse effects of diesel emissions of pHBECs. Further studies of the effect of these diesel fuel alternatives on pHBECs are required. Highlights: Increasing biodiesel percentage is diesel fuel decreases particle mass and particle number in engine emissions. Increasing triacetin percentage in biodiesel fuel increases particle number while decreasing particle mass in emissions. The addition of biodiesel and/or triacetin to diesel may be more detrimental to pHBECs than conventional diesel emissions